Perfiles aromáticos de aceites esenciales de cuatro variedades de albahaca en taiwán y estudio preliminar de su sensación aromaterapéutica (Alimentos Ciencia e Ingeniería, 2021)
Sweet basil (Ocimum basilicum L.), green basil (Ocimum basilicum L. cv. green), purple basil (Ocimum basilicum L. var. purpurascens) and clove basil (Ocimum gratissimum L.) smell similarly, and have been taken as the same plant by many for a long time. However, they are slightly different, and so are their essential oils. This study identifies the differences between these four types of plants in two aspects: first, their chemical compositions; and second, their aroma. Essential oils of these four types of plants are extracted by steam distillation. The components of the essential oils were analysed and compared using gas chromatography-mass spectrometry. Aromatherapists also evaluated the essential oils on their aroma through a questionnaire. The result shows that green basil and purple basil are very similar in terms of chemical composition and their smell and can be considered to be the same plant. Meanwhile, sweet basil, green and purple basil and clove basil have very different components and aroma and are deemed to be different types of plants.